Culture and the Quality of Government. (7th October 2019) - Porcher, Simon
Abstract: This article uses a cross‐country data set to empirically investigate the relationship between national culture and the quality of government. Culture has a strong impact on the quality of government that remains stable even after controlling for differences in institutions and economic development. This effect remains significant when the continents are considered separately, with the exception of Asia. The results reveal the importance of culture in understanding the quality of government and open new avenues for research in comparative public administration in a globalized world .